Understanding Human Fitrah Based on the Qur'an: Philosophical Foundations for Educational Development - Hazin, Burhan Ibnu; Qalyubi, Syihabuddin (JUPE : Jurnal Pendidikan Mandala, 2025)
This article examines the concept of human nature fitrah based on the Qur'an as a philosophical foundation for the development of education using descriptive-qualitative approach. Human nature, reflecting the innate inclination toward goodness, faith, and obedience to Allah, serves as a critical basis for creating a holistic education system. In the Qur'an, fitrah is described as an inherent human trait aligned with truth, as mentioned in QS. Ar-Rum: 30. The article highlights the relevance of fitrah-based education in addressing the challenges of the modern era, such as moral decline, materialism, and the erosion of spiritual values. Fitrah-based education emphasizes the balance between spiritual, moral, and intellectual dimensions to shape individuals who are not only intellectually capable but also morally upright. Through this approach, Islamic education is expected to foster a generation of faithful, virtuous individuals who actively serve as Allah’s servants and leaders on earth. This study aims to explore the concept of human nature in the Qur'an and examine its application as a philosophical foundation in developing an education system rooted in Islamic values.